Principal Management Strategies for Enhancing Teachers' Digital Literacy and the Quality of Instruction - Heri Budianto; Pardimin Pardimin; Rejokirono Rejokirono (CV. Edujavare Publishing, 2026)
The transformation of education in the digital era requires elementary schools to no longer focus solely on conventional academic achievement but also on strengthening the digital competencies of all school members, especially teachers as the primary implementers of the learning process. This study aims to analyze the principal's management strategies in improving teachers' digital literacy and the quality of learning at SD Negeri 2 Purwojati Kertek Wonosobo. The study used a qualitative approach with a descriptive type. The research subjects included the principal, teachers, and related parties at the school. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results showed that the principal's strategies were implemented through planning digital literacy improvement programs, implementing teacher training and mentoring, providing supporting facilities, and supervising and evaluating technology-based learning. The implementation of teacher digital literacy was evident in the use of digital learning media, the use of online learning resources, a variety of learning methods, and technology-based evaluations that contributed to improving the quality of learning. Supporting factors for the principal's strategies included leadership commitment, collaboration between teachers, and the availability of digital resources, while inhibiting factors included teachers' digital skill gaps, limited time, and suboptimal ongoing training. This study concluded that a planned, adaptive, and sustainable principal management strategy plays a significant role in improving teachers' digital literacy and the quality of learning in elementary schools.